A novel Bartonella-like bacterium forms an interdependent mutualistic symbiosis with its host, the stored-product mite Tyrophagus putrescentiae - Xiong, Qing; Sopko, Bruno; Klimov, Pavel B; Hubert, Jan (mSystems, 2024)
A novel Bartonella-like symbiont (BLS) of Tyrophagus putrescentiae was characterized. BLS formed a separate cluster from the Bartonella clade together with an ant symbiont. BLS was present in mite bodies (103 16S DNA copies/mite) and feces but was absent in eggs. This indicated the presence of the BLS in mite guts. The BLS showed a reduction in genome size (1.6 Mb) and indicates gene loss compared to Bartonella apis. The BLS can be interacted with its host by using host metabolic pathways (e.g., the histidine and arginine metabolic pathways) as well as by providing its own metabolic pathways (pantothenate and lipoic acid) to the host, suggesting the existence of a mutualistic association. Our experimental data further confirmed these potential mutualistic nutritional associations, as cultures of T. putrescentiae with low BLS abundance showed the strongest response after the addition of vitamins. Despite developing an arguably tight dependency on its host, the BLS has probably retained flagellar mobility, as evidenced by the 32 proteins enriched in KEGG pathways associated with flagellar assembly or chemotaxis (e.g., fliC, flgE, and flgK, as highly expressed genes). Some of these proteins probably also facilitate adhesion to host gut cells. The microcin C transporter was identified in the BLS, suggesting that microcin C may be used in competition with other gut bacteria. The 16S DNA sequence comparison indicated a mite clade of BLSs with a broad host range, including house dust and stored-product mites. Our phylogenomic analyses identified a unique lineage of arachnid specific BLSs in mites and scorpions.IMPORTANCEA Bartonella-like symbiont was found in an astigmatid mite of allergenic importance. We assembled the genome of the bacterium from metagenomes of different stored-product mite (T. putrescentiae) cultures. The bacterium provides pantothenate and lipoic acid to the mite host. The vitamin supply explains the changes in the relative abundance of BLSs in T. putrescentiae as the microbiome response to nutritional or pesticide stress, as observed previously. The phylogenomic analyses of available 16S DNA sequences originating from mite, scorpion, and insect samples identified a unique lineage of arachnid specific forming large Bartonella clade. BLSs associated with mites and a scorpion. The Bartonella clade included the previously described Ca. Tokpelaia symbionts of ants.
Keywords: Bartonella; Bacteria; kyselina lipoová; zvířata; Symbiosis; symbióza; alergeny; Mites; Animals; Thioctic Acid; Allergens; Acaridae; roztoči